Inguinal hernia containing ovary presenting as groin mass in infant (Health Renaissance, 2013)
Inguinal hernias are one of the differential diagnoses of inguinal masses in infants in both males and females. In females, an irreducible ovarian inguinal hernia tends to undergo torsion and sometimes infarction. Sonography should be used as the imaging modality of choice for the evaluation and characterization. We present a case of 19 days old female infant presented with right groin mass, diagnosed as right inguinal hernia containing right ovary on ultrasonography. Health Renaissance, January-April 2013; Vol. 11 No.1; 172-173 DOI: http://dx.doi.org/10.3126/hren.v11i2.8229